Faktor Pendukung Keberhasilan Penerapan Sistem Penjaminan Mutu Di Perguruan Tinggi - Yuli Kartika Dewi (Universitas Bunda Mulia, 2018)
ABSTRACT The aim of this study is to acknowledge the supporting factors of a successful quality management system, especially in higher education. The core of the Quality Management System is about the system that was issued by the top management to make sure all the processes done properly. ISO 9001 has set out the criteria or requirements for higher education institution applying quality management system. Formerly this standard was applied by manufacturing industries to assure their products fulfill the customer requirements. Furthermore, it would culminate the customer's satisfaction level. Meanwhile, the quality management system regulated by Indonesian Government has had an evolution, especially in the accreditation processes applied for higher education institution, which give small amount of latitude through its many standards to be accomplished by those of which operating in Indonesia. There are some factors that may support and affect the quality management system. Therefore, through this research, the researcher want to quarry the main factor that support the success of quality management system applied in the university. So,: the institution will focus all its energy to work on the key factor that influence the success of the Quality Management System in higher education. This research is applying a qualitative method. The researcher interviews some experts with plenty experiences in pioneering Quality Management System in Bina Nusantara University. As a result, the researcher finds that there many factors that determine the success of quality management system application, some of which are the leader's commitment and competencies, leadership model, excellent process and a solid team.Keywords: Quality Management System, higher education, leadership